Rancangan Penambangan Pit SR4 Pada PT. Manggala Usaha Manunggal Jobsite Bara Anugrah Sejahtera, Kabupaten Muara Enim, Provinsi Sumatera Selatan - Teguh J Alkausar; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Manggala Usaha Manunggal is a mining contractor company that is trusted to carry out coal mining activities by PT. Bara Anugrah Sejahtera in Pulau Pulau Village, Tanjung Agung Subdistrict, Darmo Village, and Keban Agung Village, Lawang Kidul District, Muara Enim Regency, South of Sumatra Province. PT. Manggala Usaha Manunggal uses the open mining method. The pit design was designed using Minescape Software 5.7. The results of pit reserves design in October 2019 were 1,225,796,571 BCM for overburden and 332,435,323 tons for coal with SR 1: 3,7. In November 2019 overburden was peeled at 1,225,026,887 and coal was mined at 322,769,945 tons with SR 1: 3,8. Whereas in December 2019 overburden was peeled at 1,238,004.473 and mined coal was 303,088.444 tons with SR 1: 4.1. Main mining equipment fleet allocation for October 2019 there are 5 fleets for overburden removal and 2 fleets for coal getting. In November 2019 there were 7 fleets for overburden removal and 3 fleets for coal getting consisting of 2 units Doosan DX700LC excavator and 1 unit Volvo EC480D excavator serve 18 units of Mitsubishi FUSO / HINO FM. In December 2019 there were 7 fleets for overburden removal and 2 fleets for coal getting.Keywords: Design Pit, Overburden, Batubara, Minescape 5.7, Fleet, Stripping Ratio